From pedagogues to teachers: balance of a decade of the curricular guidelines of the pedagogy courses in Brazil (Revista Internacional de Formação de Professores, 2016)
The national curricular guidelines that regulate Pedagogy courses in Brazil have just completed a decade. Considering the reactions that preceded the implementation of these guidelines, the epistemological incongruities perceived by many researchers, in this work it asks: which are the criticisms of the new curricular structure imposed by the guidelines on the processes of the pedagogues formation? As the epistemological doubt of Pedagogy, between being a Baccalaureate or being a course of teacher training, was experienced in the curricular organization of the referred courses? For this study, a meta-analysis was performed based on a study by Mascarenhas (2015), that used questionnaires, focus groups and documentary analysis were used in triangulation with other researches already published, based on work by Pimenta (1998, 2002, 2004), Libâneo (2000, 2006, 2010) and Franco (2008) who denounce, the problematic around a fragmented curriculum and the defense of the theoretical field of Pedagogy as the base of the formation and professional performance of the pedagogue. It was possible to verify the insufficiency of the hour load to form profiles of different professionals in a single course; as well as the characterization of the Pedagogue figure and his professional identity. The data suggest a need for a restructuring of these guidelines, and the organization of two training courses in Pedagogy courses: one focused on the teacher training, with a view to dense teacher training in the initial and early childhood education classes and another in the baccalaureate with focus in administration, coordination and school management.
Keywords: Curricular guidelines. Pedagogy. Teacher training